Multiply everything in the parenthesis by a.
ac + ab = d
Subtract ab from both sides.
ac = d - ab
Divide a on both sides.
c = d - ab / a
Hope this helps!
In logarithm, inverse operations are applied.
2n - 1 - -7n + 2 You combine like terms with subtracting
2n - 7n = -5n
-1 - 2 = -3
So -7n + 2 - 2n - 1 = -5n - 3
Answer:
(x,y) = (-2, -1)
Step-by-step explanation:
We start off by substituting the value of "x".
5x+7y=-17
x=-![\frac{5}{4} + \frac{3}{4}y](https://tex.z-dn.net/?f=%5Cfrac%7B5%7D%7B4%7D%20%2B%20%5Cfrac%7B3%7D%7B4%7Dy)
We then solve 5![5(-\frac{5}{4}+\frac{3}{4}y ) +7y= -17](https://tex.z-dn.net/?f=5%28-%5Cfrac%7B5%7D%7B4%7D%2B%5Cfrac%7B3%7D%7B4%7Dy%20%29%20%2B7y%3D%20-17)
y=-1 *Substitute the value of "y"
x= -![-\frac{5}{4}+\frac{3}{4}x(-1)](https://tex.z-dn.net/?f=-%5Cfrac%7B5%7D%7B4%7D%2B%5Cfrac%7B3%7D%7B4%7Dx%28-1%29)
x=-2
This works.
Answer: An x and y value, parenthesis around the values, and a comma in between them.
Examples of ordered pairs: (2, 5), (1872, 1683), (-3, 7), (7/8, -10/2)